Robust and consistent bonding of polydimethylsiloxane to polystyrene cell culture plates - Marta K. Orlowska; Mary Lor; Rebecca L. Fitzsimmons; Harley Robinson; Iliana Delcheva; Daniel Williams; Craig Priest; James E. Hudson (APL Materials)
Polydimethylsiloxane (PDMS) is a commonly used material for the design of new cell culture devices. Typically, molded PDMS is bonded to glass or another PDMS layer; however, it is challenging to form high-strength bonds with polymers commonly used for cell culture-ware, such as polystyrene (PS). Therefore, a robust PDMS–PS bonding method would facilitate a wider use of PDMS in tissue culture applications. Herein, we develop an irreversible, stable, and consistent PDMS–PS bonding protocol. We show that this method is superior to other currently available methods because of its bonding strength, reusability, and reliability. Furthermore, we demonstrate the utility of this bonding process in fabricating our Heart-Dyno device, a 96-well-based platform for culturing cardiac organoids. This bonding process has been successfully used over the past 2 years, with hundreds of plates manufactured for drug screening applications. Others may also have similar applications where this method may facilitate the fabrication of more robust PDMS–PS devices.